TvOneNews Online Media Framing Analysis in Ferdy Sambo Reporting’s - Rahmania, Shahnaz Mazdhatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Each media has a unique framing analysis as well as TvOneNews there is a framing analysis that is carried out in every news published, this study aims to find out the framing that was carried out in reporting on the Ferdy Sambo case and to find out how TvOneNews reconstructs the news. The results of the study show that the framing that has been carried out by TvOneNews is to be able to form a point of view of what is reported that will be broadcast to the public in the case of reporting on the Ferdy Sambo case. candrawathi is a defendant in this case. The way TvOneNews reconstructs news is by checking facts and verifying the sources used.